Synthesis of Palladium Nanowires on Flagella Template for Electrochemical Biosensor Detection of microRNA-21 - Kuo Yang; Jueyu Wang; Ying Zhang; Daizong Cui; Min Zhao (Biology)
In recent years, the use of bacterial flagella as biomimetic templates has gained increasing attention in nanomaterial synthesis due to their unique structural and functional properties. In this study, we optimized the flagella extraction method and achieved a high concentration of flagella solution. Flagella were isolated from Escherichia coli. Surface characterization revealed that the flagella had abundant functional groups, such as amino and carboxyl groups, which can serve as nucleation sites for the controlled nucleation and growth of metal nanomaterials. Using bacterial flagella as a template, we synthesized one-dimensional palladium nanowires (Fla-Pd NWs). The results of morphological and phase analyses showed that the synthesized palladium nanoparticles were uniformly and densely distributed on the surface of the flagella. Moreover, the Fla-Pd nanowires exhibited superior electrocatalytic activity, which was applied to develop an electrochemical biosensor. This biosensor was used to detect the early breast cancer biomarker microRNA-21 and exhibited a linear range of 0.66–1.98 µmol/L and a detection limit of 0.78 µmol/L. The method demonstrated high selectivity and reusability, making it a promising strategy for early cancer diagnosis.